2008
DOI: 10.3892/or.19.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and human epidermal growth receptor 2 expression in parotid mucoepidermoid carcinoma: Possible implications for targeted therapy

Abstract: Abstract. The expression of epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) was analyzed in immunohistochemical preparations from 46 primary parotid mucoepidermoid carcinomas (MEC). For the cases with lymph node metastases, the receptor expressions were investigated in parallel samples, primary tumour and metastasis, from each patient (n=11). The goal was to evaluate whether any of these receptors are suitable as a target for radionuclide-based imaging and therapy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
5
28
0
2
Order By: Relevance
“…[13] In the present study the mean of EGFR expression was 71%. [1,12,14] Hoyeck-Gebily found a positive correlation between histopathologic grading of MEC and EGFR expression, which is consistent with our results with a similar correlation (P = 0.001). [1] A review of literature shows an obvious controversy regarding the c-erbB-2 expression in MEC.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…[13] In the present study the mean of EGFR expression was 71%. [1,12,14] Hoyeck-Gebily found a positive correlation between histopathologic grading of MEC and EGFR expression, which is consistent with our results with a similar correlation (P = 0.001). [1] A review of literature shows an obvious controversy regarding the c-erbB-2 expression in MEC.…”
Section: Discussionsupporting
confidence: 94%
“…[30] A high frequency of EGFR overexpression has been reported in cancers of the head and neck region. [12] Generally, it is accepted that the overexpression of EGFR is common in salivary gland carcinomas, although in an earlier study with a small sample size, the incidence of positive EGFR staining was found to be 25% in mucoepidermoid carcinoma. [13] In the present study the mean of EGFR expression was 71%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations